2022
DOI: 10.1111/jace.18761
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photoluminescence quantum yield of Ce3+‐doped aluminum–silicate glasses for scintillation application

Abstract: Ce3+‐doped 20Gd2O3–20Al2O3–60SiO2 (GAS:xCe3+) glasses (x = 0.3, 0.7, 1.1, 1.5, 1.9 mol%) with Si3N4 as a reducing agent were prepared. The density of the glasses is around 4.2 g/cm3. With the increase in the Ce3+ concentration, both the photoluminescence (PL) and PL excitation peaks of GAS:xCe3+ glasses show a redshift because the 4f–5d energy levels of Ce3+ ions are narrowed. PL quantum yield and PL decay time of GAS:xCe3+ glasses are 28.32–50.59% and 43–64 ns, respectively. In addition, they both first incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The scintillation decay can be fitted by a double-exponential function consisting of two components (Figure (d)), a fast (∼0.075 μs, 70%) and a slow (∼0.743 μs, 30%) one. The RL decay is longer than the PL one (Figure (c)) and can be accounted for by the trap-delayed ET in Gd 3+ -mixed scintillators. ,, Further improvement in time response as well as in LY will be made possible via optimization of the Y 3+ –Gd 3+ mixing ratio, Ce 3+ concentration, and the use of aliovalent doping as well as heterostructures . Sidletskiy et al found empirically that the optimal range of the ratio of ionic radii between substitution and host ions is 1.05–1.15 to realize the greatest improvement in LY …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The scintillation decay can be fitted by a double-exponential function consisting of two components (Figure (d)), a fast (∼0.075 μs, 70%) and a slow (∼0.743 μs, 30%) one. The RL decay is longer than the PL one (Figure (c)) and can be accounted for by the trap-delayed ET in Gd 3+ -mixed scintillators. ,, Further improvement in time response as well as in LY will be made possible via optimization of the Y 3+ –Gd 3+ mixing ratio, Ce 3+ concentration, and the use of aliovalent doping as well as heterostructures . Sidletskiy et al found empirically that the optimal range of the ratio of ionic radii between substitution and host ions is 1.05–1.15 to realize the greatest improvement in LY …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they are confronted with the difficulty in mechanical processing and are particularly incompatible with the conventional fiber-drawing technique . In lieu of crystals, Ce 3+ -doped glasses have been extensively explored, thanks to their much lower production cost (about one-thirtieth of the BGO crystal), simpler processing, and being more adapted to commercialization. , Scintillator glasses are notably favorable for making large-volume detectors for future particle collider experiments (e.g., the Circular Electron Positron Collider in China). Besides, with the surging demand for oil well logging, gas exploration, and safety concerns on nuclear proliferation, the global market size is very encouraging for bulk scintillator glasses and optical fibers (with an anticipated compound annual growth rate of 4.01% from 2022 to 2027).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[51] At present, the commonly employed in glass scintillators are Ce 3+ , Tb 3+ and Eu 3+ , which are directly doped into glass matrix or doped into micro/nano crystals embedded in glass. [28,[54][55][56][57][58][59][60][61] The electronic configuration of rare earth elements can be written as [Xe]4f 0-14 5d 0-1 6s 2 . In accordance with the parity selection rules, also referred to as Judd-Ofelt theory, [62] electric dipole transition is only feasible between different parity states.…”
Section: Rare Earth Activatedmentioning
confidence: 99%